2019
DOI: 10.1200/jco.2019.37.15_suppl.4118
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lanreotide 120 mg in the treatment of clinical symptoms associated with inoperable malignant intestinal obstruction (IMIO): Results from a phase II multicenter study.

Abstract: 4118 Background: Intestinal obstruction is a severe complication in patients (pts) with digestive or gynecological cancers. For inoperable pts, there is a need to relieve symptoms and limit nasogastric tube (NGT) use. Previous studies have suggested the efficacy of somatostatin analogues in relieving obstruction-related symptoms such as nausea, vomiting and pain. Methods: This was a single arm, prospective study (NCT02275338). Pts with IMIO received one deep subcutaneous injection of LAN 120mg at day 0 (D0). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Of the 80 papers included in the review, 12 reported RCTs (2 papers reporting different outcomes for the same RCT), 3 quasi-RCTs, 8 single-arm trials and 57 observational studies with a total of 13,898 participants. For one single-arm trial not yet published, outcomes were extracted from trial results on ClinicalTrials.gov and a published abstract [22] . Study characteristics are summarised in Supplementary File 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 80 papers included in the review, 12 reported RCTs (2 papers reporting different outcomes for the same RCT), 3 quasi-RCTs, 8 single-arm trials and 57 observational studies with a total of 13,898 participants. For one single-arm trial not yet published, outcomes were extracted from trial results on ClinicalTrials.gov and a published abstract [22] . Study characteristics are summarised in Supplementary File 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Nine studies focused exclusively on patients with colorectal cancers [45,57,60,73,74,77,89,92,93] , nine studies focused on patients with gynaecological cancers [32,37,61,69,79,80,86,87,94] . [22,29] covering the same RCT; 2 Including Hardy et al, 1998 [24] (majority ovarian).…”
Section: Cancer Typesmentioning
confidence: 99%
See 3 more Smart Citations